Diario epistolare a Corrado Pavolini - Busacca, Helle (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2014)
Vulcano, Sicily 1964. After a meeting with him in Cortona, Helle Busacca, a poet and writer from Messina, began drafting an epistolary diary dedicated to Corrado Pavolini, a well-known intellectual and film director of Tuscan origins with whom she had been in love for over twenty years. Through the so far unpublished pages she dedicated to "una storia senza storia" ("a story without history"), the writer brings to life an incandescent theatre of the self, in which the dramatization of personal experience, the self-representative elaboration and the expression of a living and restless inner self combine in a mixture of strongly hybrid characters, which is conveyed by a disruptive communicative force. As the desperately pursued interlocutor becomes increasingly evanescent and unreachable, the voice of a modern tragic heroine emerges unmistakably between claim and confession.